The extent of applying transparency standard as one of the standards of governance in the human resources recruitment process: – A practical study on the Development Authority of Makkah Al-Mukarramah Region – - AlEsayi, Omar Abdulaziz; Sindi, Talat Abdel-Wahab (Journal of Economic, Administrative and Legal Sciences, 2021)
This study came with several objectives, most notably to discuss the impact of transparency as one of the standards of governance on the human resources recruitment process. To achieve the objectives of the study, the researcher followed the descriptive analytical approach, to conduct this study. The questionnaire was used as a main for collecting data from members of the study population. The study population consists of the employees of the Development Authority of Makkah Al-Mukarramah Region, whose number is 177 employees. The study found several results, the most prominent of which is the existence of a statistically significant correlation between transparency as one of the governance criteria and the human resources recruitment process in its various stages (recruitment, selection, appointment) in the Development Authority of Makkah Al-Mukarramah Region, where the correlation coefficient between transparency and the human resources recruitment process in its various stages reached a value of (0.910), Which is a very strong correlation coefficient. In light of the results of the study, the researcher recommends the need to announce in advance in all the advertising and media outlets available in the best possible way all the criteria and the criteria used to select applicants for jobs. It is also necessary to increase attention to the process of stimulating the external recruitment process to attract the best human competencies by examining the different labor market conditions.